The Communication in Social Media About COVID-19 Vaccine: Mapping and Bibliometrics Analysis - Dimas Subekti (Universitas Muhammadiyah Ponorogo, 2022)
COVID-19 emerged at the end of 2019 in China, and has spread to all corners of the world. So many parties are creating vaccines to end the COVID-19 pandemic. Simultaneously in today's digital world, there are many studies discussing the COVID-19 vaccine spread in terms of communication on social media which is the most popular social network today. Therefore, the purpose of this study is to explain global research trends related to the use of social media as a means of spreading COVID-19 vaccines, both positive and negative, from 2020 to 2021. This study uses bibliometric analysis and also uses VOSViewer to map scientific publications. This study also uses the Word frequency feature in NVIVO 12 plus. Findings in this study that the publication of scientific research on communication in social media about the COVID-19 vaccine has increased in the last two years. The mapping covers all countries whose publications are indexed by Scopus, the United States has the most significant contribution to research publications. Journal of Medical Internet Research is the journal that publishes the most research. The University of Pennsylvania is the institution that has the highest contribution. Topics that have good opportunities for future research are interpersonal, vaccination, vaccines, immunology, and COVID-19 vaccines. The narrative of global scientific research publications related to communication in social media about the COVID-19 vaccine is COVID-19, vaccine, and social media.